(untitled) (Academia Journal of Medicine, 2023)
Microorganisms must be removed from the root canal (RC) and periapical region for endodontic success. A sterile state cannot be achieved with only endodontic instrumentation. Local administration of antibiotics has been studied in light of the development of non instrumentation endodontic treatment, tissue healing and lesion sterilization. Triple antibiotic paste (TAP) with metronidazole, ciprofloxacin, and minocycline works well for non-vital young permanent teeth and the RC pathogen. Present review of literature aims to discuss role of TAP in endodontic treatment.